Male Earnings Inequality, Women’s Employment and Family Income Inequality in Australia, 1982 - 2007 - Austen, Siobhan; Redmond, G. (International Association for Research in Income and Wealth, 2010)
This preliminary paper uses cross-sectional data to examine the relationship between the growth inearnings inequality among men and women, and changes in family income inequality in Australia between 1982 and 2007-08. Although male earnings inequality increased substantially across this period, change in family income inequality was less significant. Our analysis shows that women?s earnings played a role in moderating the effects of rising male earnings inequality on the inequality of family income. This effect increased between 1982 and 2007-08, reflecting a pattern of change in women?s employment across households with low and high male earnings. The effects of this pattern of change are currently under-researched in the Australian context. Results presented in this paper have significance for understandings not only of the relationship between women?s earnings and family income inequality, but also the relationship between the hours that women work and family income inequality.